Pengaruh Burnout dan Work Life Balance Terhadap Kepuasan Kerja Serta Implikasinya Terhadap Kinerja : Survey Pada Perawat RS Prasetya Bunda di Tasikmalaya - Indrian, Elfa; Mulyana, H. Deden; Abdullah, Yusuf (LPPM STIE PPI, 2023)
Introduction/Main Objectives: To determine and analyze burnout, work life balance, job satisfaction and performance. Background Problems: In tackling Covid 19, the optimal performance of nurses is needed to heal patients by increasing satisfaction and work life balance and reducing their burnout. Novelty: research abaout work life balance in hospitals is still rare. Research Methods: The sampling technique in this study used a census sampling. This study used PLS SEM analysis with SmartPLS 3 software program. Finding/Results: Burnout had a significant positive effect on job satisfaction, work life balance had a significant positive effect on job satisfaction. Burnout has no significant effect on performance, work life balance has no significant effect on performance and job satisfaction has a positive effect on performance. Burnout and work life balance affect performance through job satisfaction. Burnout and work life balance simultaneously have a significant effect on job satisfaction. Burnout, work life balance and job satisfaction simultaneously affect performance. Conclusion: Burnout is included in the quite good category, work life balance is in the quite good category, job satisfaction is included in the quite good category and performance is included in the good category.